PERANAN MODAL DAN TENAGA KERJA TERHADAP PRODUKSI PADI SAWAH DI DESA BHUANA JAYA KECAMATAN TENGGARONG SEBERANG - Fitriah, Thoi Fatul; Djohan, Sjamsu; Lestari, Diana (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Thoi Fatul Fitriah, 2019 " the role of Capital and Labor toward lowland rice production in Bhuana Jaya village, Tenggarong Seberang District, Faculty of Economics and Business, Mulawarman University under the guidance of Sjamsu Djohan and Diana Lestari.The purpose of this research was to know the role of Capital and Labor toward lowland rice production in Bhuana Jaya village, Tenggarong Seberang in one harvest season. This research used quantitative approach  with primary data sources obtained directly from respondents by filling out the questionnaire. The analytical method used in this research was multiple linear regression with the Cobb-Douglass production function model and processed using the IBM SPSS program (Statistical Product and Service Solutions) 21.0. version.Capital had and effect toward lowland rice production 0,778, it meant that when there was an increase in capital value in 1 percent, it would increase 0,778 percent of the production. It showed a positive and significant relationshop. The labor had an influence toword the production of lowland rice for 0,281, it meant that when there was an increase in the number of the labor in 1 percent, it would increase 0,281 percent of lowland rice production. It showed a positive and significant relationship.